Studies in Safavid mind, society, and culture - Reid, James J; Yazdani, Mehri (Costa Mesa, CA : Mazda Publishers, 2000)
"Studies in Safavid Mind, Society, and Culture examines Safavid-era society from the vantage points of literary and artistic sources. The work studies Safavid society from its pinnacle in the monarchy, to the military elite households, merchants, tradesmen, rural populations, and the lower orders of society including the underworld."--Jacket
Social theory: Persia, 1200-1700 -- Psychological perspectives in Safavid sources -- Upper orders of Safavid society -- Social and cultural history of the lower orders -- Criminality, the underworld in Safavid society -- Persian artistic representations within a social interest
Includes bibliographical references (pages 407-419) and index
Keywords: Social classes -- Iran -- History; Social groups -- Iran -- History; Iran -- History -- Ṣafavid dynasty, 1501-1736